Beyond Language Proficiency: Raising Awareness of Women's Empowerment Through English Language Teaching - Zaitun Qamariah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This article underlines the significance of teaching the English language to raise awareness of women's empowerment. It explores beyond the basic understanding of language proficiency to educate on gender issues and encourage progressive action. By reviewing the literature, the article identifies effective teaching strategies for discussing women's empowerment issues in the context of English language learning. This article aims to contribute to raising social awareness and inspire concrete actions towards achieving gender equality. In an increasingly complex and globalized society, understanding the importance of women's role in development is critical to achieving sustainable and inclusive development.